2019
DOI: 10.1016/j.apergo.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Shoe microclimate: An objective characterisation and subjective evaluation

Abstract: Shoe microclimate (temperature and humidity) has been suggested to contribute to perceptions of foot thermal comfort. However, limited data is available for perceptual responses in relation to shoe microclimate development both over time and within different areas of the shoe. This study evaluates perceptions of foot thermal comfort for two running shoes different in terms of air permeability in relation to temporal and spatial characteristics of shoe microclimate. The temporal characteristics of shoe microcli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 27 publications
1
53
0
Order By: Relevance
“…Besides the selected 15 candidate questionnaires, participants also recommended other questionnaires which might be useful for comfort research. They are: 1) Shoe microclimate evaluation questionnaire [ 15 ]; 2) Situation awareness global assessment technique (SAGAT) [ 16 ]; 3) Methodologies for subjective evaluations of indoor environment in ISO 15251 [ 17 ]; 4) The scale used in ESI virtual seat solutions (PAM comfort) [ 18 ]; 5) the Kano model [ 19 ] and 6) Multifactorial assessment of comfort of clothing [ 20 ]. It is noted that whilst these questionnaires may be very useful for their targeted applications, they are difficult to apply outside of their application area focus.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the selected 15 candidate questionnaires, participants also recommended other questionnaires which might be useful for comfort research. They are: 1) Shoe microclimate evaluation questionnaire [ 15 ]; 2) Situation awareness global assessment technique (SAGAT) [ 16 ]; 3) Methodologies for subjective evaluations of indoor environment in ISO 15251 [ 17 ]; 4) The scale used in ESI virtual seat solutions (PAM comfort) [ 18 ]; 5) the Kano model [ 19 ] and 6) Multifactorial assessment of comfort of clothing [ 20 ]. It is noted that whilst these questionnaires may be very useful for their targeted applications, they are difficult to apply outside of their application area focus.…”
Section: Resultsmentioning
confidence: 99%
“…The protocol employed has previously been used to objectively characterize shoe microclimate and perceptual responses for permeable and impermeable running shoes. 5…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Tactile interactions which occur when materials come into contact with the human body are important in the perception of wetness when wearing apparel 26,27 and footwear. 5,28 Our previous experimental work 28 has shown that the perception of wetness and comfort at the foot is not dominated by regions of high sweat production but rather by tactile cues caused by foot movement in the shoe. Areas of low sweat production (toes and heel) were perceived as being wetter, stickier and more uncomfortable than the dorsal and plantar foot regions (areas of high sweat production) due to the expected higher contact loads and propulsion actions experienced and required at these regions during running.…”
Section: Should We Wear Socks?mentioning
confidence: 99%
See 2 more Smart Citations